Strengthening the Role of Case Manager in Quality and Cost Control in Hospital: A Case Study at Sembiring General Hospital, Deli Serdang, North Sumatra - Efrata Efrata; Alprindo Sembiring; Friska Ernita Sitorus (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Case managers in hospitals play a vital role in keeping healthcare services both high in quality and efficient in cost. With the financing system now using a packaged fee model, hospital leaders are under pressure to manage expenses effectively without compromising patient care. This study looks at how the case manager function is carried out at Sembiring General Hospital and explores the challenges faced in practice. Conducted in April 2025, the research used a qualitative case study approach with six informants: five case managers and one medical services director. Data were collected through semi-structured interviews and were analyzed thematically. Findings show that case managers encounter two main sets of challenges: organizational issues and professional care provider (PPA) issues. On the organizational side, the obstacles include limited IT/data support, unclear authority, and insufficient training. On the PPA side, challenges involve physicians’ willingness to accept input, collaboration among care providers, and adherence to clinical pathways. To strengthen the role of case managers, hospital management needs to reinforce their authority across all service units, especially among patient care professionals. Practical steps include adding a dedicated menu in the hospital information system (SIM RS) so case managers can monitor costs in real time, and issuing a director’s decree to formally confirm their duties and authority. These measures are essential to optimize case managers’ contribution to cost and quality control Keywords: The Role of Case Manager, Quality and Cost Control, Professional Care Provider